Quality Improvement and Safety in US Pharmacy Schools - McManus, Katherine (Am J Pharm Educ, 2019)
Objective. To catalog the methods in which quality improvement (QI) and safety are taught in schools and colleges of pharmacy in the United States and showcase exemplar QI programs. Methods. This descriptive, multi-phase study included an online questionnaire, syllabi review, and phone interviews. The study was approved by the University of Arizona Institutional Review Board (IRB). One representative from each US pharmacy school accredited by the Accreditation Council for Pharmacy Education (ACPE) was invited to participate. Participants indicated the type of QI education their school provided via online questionnaire. Following questionnaire completion, syllabi were requested from the schools and phone interviews were scheduled with a school representative to obtain additional information. From the data, exemplars were chosen using a predetermined, evidenced-based rubric. Results. Of the 136 schools contacted, 56 (41.2%) completed the survey. Of the responding schools reporting their QI and safety offerings, 41 (73.2%) had a required session/module; 24 (42.9%) had a required course; 21 (37.5%) had an elective course; 21 (37.5%) had an introductory pharmacy practice experience (IPPE), advanced pharmacy practice experience (APPE), or internship; 17 (30.4%) had a required project; 17 (30.4%) had interprofessional education integrated into their course; 15 (26.8%) had an error laboratory; and 11 (19.6%) offered postgraduate training. Conclusion. Many of the responding US schools of pharmacy expose students to some aspect of QI and/or safety, most often via class session or module. The exemplar programs serve as examples of how QI can be further integrated into pharmacy curricula.